PICTURING THE INDIAN TIGER: IMPERIAL ICONOGRAPHY IN THE NINETEENTH CENTURY. Issue 3 (6th June 2014) - Crane, Ralph; Fletcher, Lisa; Gibson, Mary Ellis; Richard, Melissa
<x content-type="archive" xml:space="preserve">Abstract</x> In The Empire of Nature John M. MacKenzie suggests there were "three animals in India with which the British had a special hunting relationship, the tiger, the elephant and the pig" (179). Of these, the tiger is the one most closely associated with Britain's imperial relationship with India. By the mid nineteenth century, as Joseph Sramek explains, "tigers . . . had become invested with several potent meanings" (659). Several critics including Sramek and Annu Jalais demonstrate how tigers were closely associated with Indian rulers, and, at the same time, with all that was wild and untamed about the subcontinent. Thus "[o]nly by successfully vanquishing tigers would Britons prove their manliness and their fitness to rule over Indians" (Sramek 659). Through close readings of selected tiger images from the second half of the nineteenth century, this paper considers the way tigers were consistently used as visual signifiers of India in a series of stock-in-trade images which depict tiger hunts, white men protecting white women from tigers, and tigers menacing Indians.